Physiological and transcriptomic analyses of response of walnuts (Juglans regia) to Pantoea agglomerans infection - An, Xiu-Hong; Wang, Ning; Wang, Hongxia; Li, Yan; Si, Xiao-Yu; Zhao, Shugang; Tian, Yi (Frontiers in Plant Science, 2023)
Introduction: Walnut blight is a serious bacterial disease that affects the yield and quality of walnuts. Pantoea agglomerans is one of the main causative agents of walnut blight. However, there have been few studies on the response of walnuts to P. agglomerans infection.Methods: In this study, the soluble sugar, photosynthesis, antioxidant enzyme activities, secondary metabolite were measured, and the transcriptomic analysis was performed to determine the response of walnut tissue cultures to P. agglomerans infection.Results: After pathogen inoculation, the soluble sugar content decreased, and photosynthesis was inhibited. Antioxidant enzyme (superoxide dismutase and peroxidase) activities and secondary metabolite (phenol and flavonoid) contents increased, especially in the early stages of inoculation. Transcriptomic analysis revealed that the phenylpropanoid biosynthesis pathway is induced after infection, and pathogen infection promotes ABA and ethylene signal transduction and inhibits auxin signalling. In addition, SA and JA-related gene expression was altered after inoculation with P. agglomerans, and the FLS-and calcium-mediated disease resistance signalling pathways were activated. Furthermore, our results suggest an involvement of the R-protein RPM-mediated disease resistance pathway in the response of walnuts to bacterial infections. Discussion: Our findings indicated that phenylpropanoid biosynthesis, hormone signal transduction, and plant-pathogen interaction have key roles in pathogenic inoculation, which provide insights into the molecular mechanisms in the response of walnuts to P. agglomerans infection.